Influence of gastric banding on quality of life in morbid obesity patients (Ожирение и метаболизм, 2011)
The aim of the study was unification of the results and specification of indications for different kinds of bariatric operations. In our study we performed a comparative analysis of the quality of life with Moorehead-Ardelt II system and sweet eating syndrome in 45 patients after stomach banding for morbid obesity